Securing the Cloud: Threats, Attacks and Mitigation Techniques - Alani, Mohammed M. (Journal of Advanced Computer Science & Technology, 2014)
This paper is aimed to present information about the most current threats and attacks on cloud computing, as well as security measures. The paper discusses threats and attacks that are most effective on cloud computing such as data breach, data loss, service traffic hijacking..etc. The severity and effect of these attacks are discussed along with real-life examples of these attacks. The paper also suggests mitigation techniques that can be used to reduce or eliminate the risk of the threats discussed. In addition, general cloud security recommendations are given.Keywords: cloud, cloud computing, security, threats, attacks, SaaS, PaaS, IaaS.